Patient Overall Satisfaction derived from the Service Quality and Sources of Expectation in the Health Service Company - Wandebori, Harimukti (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2017)
This study aims to explore the service quality using the variables of Hierarchical Model of Health Service Quality and probed its interaction to the patient satisfaction in Mutiara Bunda Women and Child Hospital Salatiga. The SERVQUAL method was employed as the mean to evaluate the service quality. Additionally, the sources of expectation were also being investigated to see how the patients set their initial expectation. The quantitative method would be used through aquestionnaire to the patient in the hospital. The result indicates that the perception-expectation gap of health service quality in some extent significantly contributed to the overall satisfaction. The previously-determined sources of expectation also significantly contributed in shaping the overall expectation of patient. This research will contribute to the academical and practical realm in investigating the connection between service quality and customer satisfaction in the health care service industry. Furthermore, this research exhibits the novelty in which the new set of variables isapplied in assessing the service quality by finding out the gap score. This will also increase the awareness of the hospital to improve the service quality in order to improve patient satisfaction which leads to loyal patient cultivation.